Minat Belajar Siswa dalam Mengikuti Pembelajaran Pendidikan Agama Kristen di Kelas VII SMP Negeri 3 Palangka Raya - Nadia Antika Sari; Matius Timan Herdi Ginting (Harati: Jurnal Pendidikan Kristen, 2023)
Interest in learning plays an important role in the student learning process. Students who have a low interest in learning, the quality of learning will decrease and will affect student learning outcomes. The purpose of this research was conducted to describe students' interest in learning Christian education in class VII SMP Negeri 3 Palangka Raya and find out the factors that cause a lack of interest student learning in participating in Christian Religion education lessons in class VII SMP Negeri 3 Palangka Raya. Qualitative research approach with descriptive research. Data collection techniques through observation, questionnaires and documentation. The results showed 1) 5 (39%) students with low learning interest, 5 (38%) students with moderate learning interest and 3 (23%) students with high learning interest. 2) Factors causing the lack of interest in student learning, from internal factors, health, disabilities and internal motivation. External factors include teaching tools and teaching methods.